FILSAFAT HUKUM ISLAM DAN ILMU-ILMU SHARI>’AH METODOLOGIS - Herfin Fahri (LPPM Institut Agama Islam Al-Hikmah Tuban, 2016)
Approachment of philoshophy or ideology in Islamic Law or philoshophy law use by careful with classical and contemporary religious sholars (‘ulama> ). The word of pholoshophy (falsafah) is not found in sources of Islamic law. Although not found in sources of Islamic law, however the meaning of pholoshophy (falsafah) in Ulama’s perspective is similar meaning with hikmah. Therefore. For understanding and seek the knowledge of Islamic law, someone must need the methodologies to understand it. Al-Qawa>’id al-Fiqhiyyah (legal principles) as deductive reason in legal reasoning through usu>l al-fiqh approach. This paper seeks to answer a problem of how deductive reson using Al-Qawa>’id al-Fiqhiyyah is regarded as the sourch of Islamic law in the perspective of classical and contemporary religious sholars (‘ulama> ). Basing mainly on the legal approach , this paper argues that not all ulama> are familiar with, and therefor, employ Al-Qawa>’id al-Fiqhiyyah in the making of Islmaic legal opinion. Permitting the use of legel principle as reference on the condition should be drived from thr primary source of Islamic law (al-Qur’a>n dan Sunnah), not from the legal thought of jurists.